Characteristics of fermented Cassava Flour as Material for Producing Sagukasbi - Rasulu, Hamidin; Yuwono, Sudarminto S.; Kusnadi, Joni (Jurnal Teknologi Pertanian, 2012)
This research aimed to study the effects of two fermentation methods (fixed and unfixed) on HCN content, bulk density, moisture content, flour microstructure, and sensory properties of texture, colour, and flavor of cassava flour made from local cassava tuber of Tidore variety. Unfixed fermentation was conducted by replacing soaking water every one a day. Meanwhile at fixed fermentation, the soaking water was not replaced. The result showed that HCN content of cassava flour of fixed fermentation method was significantly lower than (p<0.05) on unfixed fermentation method. Moisture and starch content of fixed and unfixed fermented cassava flour was lower than unfermented cassava flour. Starch granule micrograph of fixed and unfixed fermented cassava flour had similar starch granule size. Texture, color, flavour of both fermented cassava flour did not differ significantly (p>0.05). Otherwise, fixed fermentation method using local cassava variety of Tidore could be suggested for producing cassava flour and was recommended as raw material for sagukasbi processing. Keywords: fermented cassava, sagukasbi, microstructure, starch granule, cassava flour, unfixed fermen-tation, fixed fermentation, HCN content